Cabozantinib in combination with atezolizumab in patients with metastatic castration-resistant prostate cancer: results from an expansion cohort of a multicentre, open-label, phase 1b trial (COSMIC-021). Issue 7 (July 2022) - Agarwal, Neeraj; McGregor, Bradley; Maughan, Benjamin L; Dorff, Tanya B; Kelly, William; Fang, Bruno; McKay, Rana R; Singh, Parminder; Pagliaro, Lance; Dreicer, Robert; Srinivas, Sandy; Loriot, Yohann; et al.
Summary: Background: Patients with metastatic castration-resistant prostate cancer have few treatment options after novel hormonal therapy (eg, abiraterone or enzalutamide). We aimed to evaluate cabozantinib, a tyrosine kinase inhibitor with immunomodulatory properties, in combination with the PD-L1 inhibitor atezolizumab in metastatic castration-resistant prostate cancer. Methods: COSMIC-021 is an ongoing, multicentre, open-label, phase 1b study with a dose-escalation stage followed by tumour-specific expansion stages. Expansion cohort 6 in metastatic castration-resistant prostate cancer was enrolled at 42 cancer research centres in France, Italy, the Netherlands, Spain, and the USA. Eligible patients were aged 18 years or older and had metastatic castration-resistant prostate cancer with radiographic soft tissue progression following treatment with either enzalutamide or abiraterone, or both; measurable soft tissue disease per Response Evaluation Criteria In Solid Tumours (RECIST) version 1.1; and an Eastern Cooperative Oncology Group performance status of 0 or 1. Patients received oral cabozantinib 40 mg per day and intravenous atezolizumab 1200 mg once every 3 weeks. Study treatment continued until progressive disease or unacceptable toxicity. All enrolled patients were assessed for efficacy and safety. The primary endpoint was objective response rate per RECIST version 1.1 as assessed by the investigator. This study is registered with ClinicalTrials.gov, NCT03170960 . Findings: Between April 24, 2018, and Aug 31, 2020, 132 patients were enrolled and received at least one dose of study treatment. At data cutoff (Feb 19, 2021), median duration of follow-up was 15·2 months (IQR 9·6–21·7). Objective response rate was 23% (95% CI 17–32; 31 of 132 patients), with three (2%) confirmed complete responses and 28 (21%) confirmed partial responses. 72 (55%) of 132 patients had grade 3–4 treatment-related adverse events, with the most common being pulmonary embolism (11 [8%] patients), diarrhoea (nine [7%]), fatigue (nine [7%]), and hypertension (nine [7%]). There was one grade 5 treatment-related adverse event (dehydration). 74 (56%) of 132 patients had serious adverse events of any causality. 28 (21%) of 132 patients had treatment-related adverse events leading to discontinuation of either study drug. Interpretation: Cabozantinib plus atezolizumab showed promising antitumour activity in patients with metastatic castration-resistant prostate cancer after novel hormonal therapy with an acceptable safety profile, supporting further evaluation of this combination. Funding: Exelixis.